We Have Always Been Hybrids (and Donald Duck Knows It) - Marrone, Gianfranco (E|C, 2023)
The notion of hybrid in Latour's works depends on whether we see it as a problem of terminology, metalanguage, methodology or conceptualisation. By distinguishing these different points of view, this essay will attempt to disambiguate the notion of the hybrid by showing, behind its apparent simplicity, its profound semantic complexity and also some critical points. Through recourse to the analysis of a Donald Duck Disney cartoon, it will be shown how semiotic theory, in particular narrative and passion semiotics, can further articulate, and at various levels, what is meant by hybrid finally hopefully demonstrating that hybridisation is a procedure inherent to all human and social stories.